DESIGN OF DIGITAL PRAYER CLOCK BASED ON RASPBERRY PI 3 - Dodi Yudo Setyawan; M Rafiq; Triowali Rosandy; Suratno - (Proceeding International Conference on Information Technology and Business, 2018)
Prayer is an obligation that must be carried out by every Muslim, at least five times a day a night is obliged to pray. The time was determined according to the Qur'an and the hadith of the Prophet. Every Muslim must know the prayer times precisely and specifically for the muezzin to proclaim the call to prayer. Determining prayer times is largely dependent on the position of the sun on the earth. This certainly makes it difficult to determine the exact prayer time, therefore it is necessary to build a system that is able to determine and display prayer times precisely based on raspbarry pi3. Determination of prayer times is based on the position of longitude and latitude of the earth according to real time and altitude. Built using lazarus programming language with free pascal compiler. The system can determine and display prayer times precisely.Keywords: Prayer, digital, raspberry